PENYULUHAN TENTANG BAHAYA CACINGAN PADA ANAK DI DESA COT BEUT KECAMATAN KUTA BARO KABUPATEN ACEH BESAR - Zuhkrina, Yuli; Muharrina, Cut Rahmi; Marjunita; Nurlaila; Sastika, Omi; Ridha, Sri Eva; Hastuti, Dewi (Transpublika Publisher, 2021)
Be aware and recognize worm disease in children. This disease that often occurs is very disturbing the development of children. So, it is very important to recognize and prevent worm disease in children from an early age. The disturbances can range from mild without symptoms to severe and even life-threatening. In general, nutritional disorders or anemia can occur in patients. This will indirectly lead to impaired intelligence in children. About 60 percent of Indonesians have worm infections. The most age group is in the age of 5-14 years. The prevalence rate is 60 percent, 21 percent of which attack elementary school-aged children and the average content of worms per person is six. The data was obtained through surveys and research conducted in several provinces in 2006. The method used is Pre Test and Post Test using a questionnaire. Based on the results of the counseling there was an increase in respondents' knowledge of the dangers of intestinal worms in children, namely in the good category as many as 39 (76,47%). The conclusion is that there is a significant increase in respondents' knowledge after being given counseling.